Adubação de sistemas para a cultura do milho em sistema integrado de produção agropecuária - Korb, Daniel Vinicius (2023)
The work was conducted at the Federal Technological University of Paraná - UTFPR, Dois Vizinhos Campus, during the agricultural year 2021/2022. The objective was to evaluate the influence of residual fertilization of N, P, and K applied to the winter pasture on corn (Zea mays) in an integrated crop-livestock production system (SIPA). The treatments were arranged in split-plot design (3x4x5 trifactorial scheme). In the winter, the entire area received N, P, and K fertilization (400 kg/ha of 05-20-10 formulated fertilizer (NPK) and 120 kg of N/ha broadcast), at the planting of forage species consisting of a consortium of oats (Avena strigosa S.) + ryegrass (Lolium multiflorum L.) + vesicular clover (Trifolium vesiculosum Savi). The treatments during the pasture cycle consisted of two levels of animal supplementation: supplementation at 0.3% of live weight, supplementation at 0.5% of live weight, and a control without supplementation. In the summer, four subplots with different doses of phosphorus and potassium (0, 30-20, 60-40, and 90-60 kg/ha of P2O5 and K2O, respectively) were allocated for each plot from the winter. In each P and K fertilization subplot, five sub-subplots with nitrogen doses (0, 75, 150, 225, and 300 kg/ha) were applied as topdressing to the corn crop, broadcast in the form of urea (46% N). Soil chemical attributes and corn biomass yield were evaluated. After the winter, it was observed that the residual effect of fertilization was very efficient, significantly increasing soil phosphorus levels (from 21.4 to 44.1 mg/dm³) and potassium levels (from 0.60 to 0.72 cmolc/dm³) at a depth of 0-20 cm, with no differences observed between the levels of supplementation provided to beef cattle. After the corn cycle, it was not possible to evaluate grain production according to the fertilization doses due to the long period of drought that affected the corn crop. The levels of P and K present in the soil were evaluated, and the results indicate that SIPAs are very efficient in the long term. Phosphorus showed 58.7% efficiency during the pasture phase and an average of 33% efficiency during the corn crop. Meanwhile, potassium exhibited 80.8% efficiency during the pasture cycle, highlighting the system's stability.